Direct metabolite detection with an n-type accumulation mode organic electrochemical transistor - Pappa, Anna Maria; Ohayon, David; Giovannitti, Alexander; Maria, Iuliana Petruta; Savva, Achilleas; Uguz, Ilke; Rivnay, Jonathan; McCulloch, Iain; Owens, Róisín M; Inal, Sahika (My University, 2018)
The inherent specificity and electrochemical reversibility of enzymes poise them as the biorecognition element of choice for a wide range of metabolites. To use enzymes efficiently in biosensors, the redox centers of the protein should have good electrical communication with the transducing electrode, which requires either the use of mediators or tedious biofunctionalization approaches. We report an all-polymer micrometer-scale transistor platform for the detection of lactate, a significant metabolite in cellular metabolic pathways associated with critical health care conditions. The device embodies a new concept in metabolite sensing where we take advantage of the ion-to-electron transducing qualities of an electron-transporting (n-type) organic semiconductor and the inherent amplification properties of an ion-to-electron converting device, the organic electrochemical transistor. The n-type polymer incorporates hydrophilic side chains to enhance ion transport/injection, as well as to facilitate enzyme conjugation. The material is capable of accepting electrons of the enzymatic reaction and acts as a series of redox centers capable of switching between the neutral and reduced state. The result is a fast, selective, and sensitive metabolite sensor. The advantage of this device compared to traditional amperometric sensors is the amplification of the input signal endowed by the electrochemical transistor circuit and the design simplicity obviating the need for a reference electrode. The combination of redox enzymes and electron-transporting polymers will open up an avenue not only for the field of biosensors but also for the development of enzyme-based electrocatalytic energy generation/storage devices.
Keywords: Amperometric sensors; Biomolecules; Biosensors; Electrochemical electrodes; Electrons; Enzyme electrodes; Enzymes; Ions; Metabolites